Cultural Developments During The Meiji Era 1868-1912 (Journal of the College of Basic Education, 2024)
Japan enjoyed relative peace for a period of time as a result of its geographical nature, which enabled it to live in isolation from the outside world for about 250 years, but this did not lose its connection with the outside world, so it was able to bring from some Asian countries the various civilizations and cultures that prevailed at the time, and adapted them to suit the conditions and traditions of Japanese society, as the Japanese had the ability to digest foreign cultural influences while preserving the values they inherited from their ancestors, and after breaking the isolation, foreign cultures began to flow to its lands, and after the emperor ascended the Meiji throne of the Empire of Japan introduced reforms that included all aspects and brought about deep transformations in the structure of Japanese society, and it marked the beginning of a wide openness to Western cultures, to blend the authentic cultural heritage of Japanese civilization with the culture coming from the West, which produced a new national culture of modern Japan.